Risk Factors Associated with Hyporesponsiveness to Erythropoietin in Chronic Kidney Disease Patients on Hemodialysis Who Present Anemia: A Multicenter Case-Control Study - Carlos Perez Tulcanaza; André Benítez-Baldassari; Andrea Banegas-Sarmiento; Sánchez Redrobán, José (My University, 2025)
Background: Anemia represents a significant complication in patients with advanced chronic kidney disease (CKD) on hemodialysis, primarily caused by reduced renal erythropoietin production. Despite erythropoiesis-stimulating agents (ESAs) being the cornerstone of treatment, hyporesponsiveness to these agents remains a clinical challenge with implications for patient outcomes. Objective: To identify and quantify risk factors associated with hyporesponsiveness to erythropoietin in patients with CKD on hemodialysis who present with anemia. Methods: This multicenter case–control study analyzed data from 784 hemodialysis patients receiving erythropoietin therapy across six dialysis centers in Ecuador between January and December 2019. Hyporesponsiveness was defined as requiring ≥ 200 IU/kg/week of erythropoietin alfa for ≥3 consecutive months to maintain target hemoglobin levels (10–12 g/dL). Demographic, clinical, and laboratory parameters were compared between hyporesponsive cases (n = 123) and responsive controls (n = 661). Bivariate and multivariate logistic regression analyses were performed to identify independent risk factors. Results: The prevalence of erythropoietin hyporesponsiveness was 15.69%. A multivariate analysis identified female sex (adjusted OR = 1.96; 95% CI: 1.20–3.20; p < 0.001), age < 50 years (adjusted OR = 4.25; 95% CI: 2.42–7.47; p < 0.001), serum albumin < 4.0 g/dL (adjusted OR = 10.53; 95% CI: 6.53–16.98; p < 0.001), ferritin ≥ 800 ng/mL (adjusted OR = 7.28; 95% CI: 4.22–12.57; p < 0.001), transferrin saturation < 20% (adjusted OR = 9.27; 95% CI: 5.47–15.69; p < 0.001), parathyroid hormone ≥ 500 pg/mL (adjusted OR = 1.89; 95% CI: 1.16–3.09; p = 0.011), and use of renin–angiotensin system blockers (adjusted OR = 2.25; 95% CI: 1.36–3.71; p = 0.002) as independent risk factors for erythropoietin hyporesponsiveness. Conclusions: Multiple demographic, clinical, and laboratory factors independently contribute to erythropoietin hyporesponsiveness in hemodialysis patients. Identification of these risk factors may guide clinicians in developing individualized treatment approaches, optimizing erythropoietin dosing, and implementing targeted interventions to improve anemia management in this vulnerable population.